2022
DOI: 10.1155/2022/5188006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Circulating Tumor Cells (CTCs) and Survivin on Predicting Prognosis in Thyroid Cancer Patients

Abstract: Background. Clinical significance of circulating tumor cell (CTC) count, mesenchymal CTCs (MCTCs), and survivin in patients with thyroid cancer remains unclear. We evaluated the relationship between the expression of different CTC subtypes or survivin and the prognosis in patients with thyroid cancer. Patients and Methods. This study enrolled 164 patients with thyroid cancer who were diagnosed from January 2013 to September 2020 in our hospital. Among these patients, there were 73 cases with papillary thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Successful CTC detection has been achieved for most solid tumor types, and CTC counts are correlated with patient prognosis and with the risk of recurrence or metastasis [6,7]. CTC detection has previously been used to evaluate patients with breast, prostate, thyroid, renal, and colon cancers [8][9][10]. While CTCs have clear relevance to disease status in individual patients, prior work suggests that only 28.6% of CRC patients exhibits a detectable CTC burden (>1 per 7.5 ml of blood) among Chinese and Western populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Successful CTC detection has been achieved for most solid tumor types, and CTC counts are correlated with patient prognosis and with the risk of recurrence or metastasis [6,7]. CTC detection has previously been used to evaluate patients with breast, prostate, thyroid, renal, and colon cancers [8][9][10]. While CTCs have clear relevance to disease status in individual patients, prior work suggests that only 28.6% of CRC patients exhibits a detectable CTC burden (>1 per 7.5 ml of blood) among Chinese and Western populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…CTC evaluation has been investigated also in MTC with promising results (Table 1). In 2022, in a cohort of 12 MTC patients out of 164 patients (7.3%), Weng and colleagues [23] evaluated the number of CTCs at diagnosis using the CanPatrol capture technique and found that 58.3% (7/12 MTC patients) were CTC-positive while 5/12 (41.6%) were not. The authors considered a cutoff of six CTCs and found that, in that case, patients had shorter progression-free survival and an increased metastasis rate.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…CTCs display both spatial and temporal heterogeneity when compared to the primary tumor. At the single-cell level, CTC omics analysis can be performed in several tumor subtypes [169], including prostate, breast, lung, thyroid and colorectal cancers [170][171][172][173][174][175]. Each isolated CTC can provide crucial information concerning the clinical and therapeutic scenario for any individual patient.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%